STRUCTURE OF THE INFORMATION COMPETENCE OF FUTURE TEACHERS OF ENGINEERS SEWING PROFILE - Seydametova, З.Н. (Journal of Information Technologies in Education (ITE), 2012)
In the article the component structure of information competency of future engineers and educators, which builds on the personal, cognitive, operational activity-related, reflexive and evaluative components.